2007
DOI: 10.1093/aje/kwm182
|View full text |Cite
|
Sign up to set email alerts
|

Malathion Exposure and the Incidence of Cancer in the Agricultural Health Study

Abstract: Malathion is the most common organophosphate insecticide applied in the United States, and while some studies suggest that it may be clastogenic, its carcinogenicity has not been demonstrated in rodents. However, malathion has been associated with non-Hodgkin's lymphoma in several epidemiologic studies. The authors investigated associations between malathion exposure and cancer among 19,717 pesticide applicators enrolled in the Agricultural Health Study between 1993 and 1997. Information on lifetime years and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(89 citation statements)
references
References 56 publications
1
84
0
4
Order By: Relevance
“…Majority of the respondents use phostoxin which can be used as rodenticide or fumigants in preserving their produce. This was in line with what [15,16] reported that, the commonly used aluminium phosphide are phostoxin, Quickphos and Fumitox. The most commonly used Organophosphates include; DDforce, chlorpyrifos, parathion and malathion.…”
Section: Discussionsupporting
confidence: 92%
“…Majority of the respondents use phostoxin which can be used as rodenticide or fumigants in preserving their produce. This was in line with what [15,16] reported that, the commonly used aluminium phosphide are phostoxin, Quickphos and Fumitox. The most commonly used Organophosphates include; DDforce, chlorpyrifos, parathion and malathion.…”
Section: Discussionsupporting
confidence: 92%
“…Malathion is an insecticide which is widely used in agriculture, residential landscaping and public recreation areas. On the other hand, Malathion is known for his toxicity to humans [23] and thus it is important to monitor and control its concentration in drinking water, agriculture products and the environment.…”
Section: Resultsmentioning
confidence: 99%
“…Otros efectos de la exposición crónica a plaguicidas que presentan una contundente evidencia son las enfermedades neurológicas, como Parkinson, esclerosis lateral amiotrófica y Alzheimer(12,24-28) y el desarrollo de algunos tipos de cáncer como leucemia, cáncer de próstata y el linfoma de Hodgkin (12,(29)(30)(31)(32)(33)(34)(35). Las investigaciones han encontrado que existe un mayor riesgo de presentar estas enfermedades si se vive en áreas rurales, se bebe de agua de pozo y se trabaja en actividades agrícolas.…”
Section: El Problema Histórico De Los Plaguicidasunclassified